PENGARUH SALINITAS YANG BERBEDA TERHADAP PERTUMBUHAN DAN SINTASAN BENIH IKAN BAUNG (Hemibagrus nemurus) - Teguh Oktavian; Rosyadi; Khairul Hadi (DINAMIKA PERTANIAN, 2023)
This study aims to determine the effect of different salinities on the growth and survival of baung fish (Hemibagrus nemurus) fry. The method used is an experimental method with a complete random design (RAL) consisting of 5 treatments with 3 repeats, namely P1 = salinity of 3 ppt, P2 = 4 ppt, P3 = 5 ppt, P4 = 6 ppt, and P5 = 7 ppt. The results showed the best treatment in P4 treatment of baung fry rearing with a salinity of 6 ppt, resulting in absolute weight growth of 0.73±0.04 gr, absolute length of 1.88±0.19 cm, daily growth rate of 3.50±0.19%, feed conversion of 1.69±0.08, and survival of 98±3.46%. The range of water quality during maintenance was supportive for baung fry, with temperatures ranging from 25–28 0C, pH 6.2–6.78, dissolved oxygen content 6.0–7.7 mg/L, and ammonia ranged from 0.59–1.88 mg/L.